2019
DOI: 10.1101/733709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A molecular switch for Cdc48 activity and localization during oxidative stress and aging

Abstract: Control over a healthy proteome begins with the birth of the polypeptide chain and ends with coordinated protein degradation. One of the major players in eukaryotic protein degradation is the essential and highly conserved ATPase, Cdc48 (p97/VCP in mammals). Cdc48 mediates clearance of misfolded proteins from the nucleus, cytosol, ER, mitochondria, and more. Here we dissect the crosstalk between cellular oxidation and Cdc48 activity by identification of a redox-sensitive site, Cys115. By integrating proteomics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Pichia pastoris E GSH roGFP1 [37,197] roGFP1-iE [37,197,198] roGFP1-iL [198] general redox state Redoxfluor [44] Saccharomyces cerevisiae E GSH rxYFP [31,43,46,[199][200][201] roGFP1 [25][26][27][28][29]202,203] roGFP2 [12,19,33,[204][205][206] roGFP [207] eroGFP [35,36,[38][39][40][41][42]208] Grx1-roGFP2 [15,24,32,47,48,[209][210][211][212][213][214] general redox state rxRFP [30] Redoxfluor [44,215] H 2 O 2 HyPer…”
Section: Fungimentioning
confidence: 99%
See 3 more Smart Citations
“…Pichia pastoris E GSH roGFP1 [37,197] roGFP1-iE [37,197,198] roGFP1-iL [198] general redox state Redoxfluor [44] Saccharomyces cerevisiae E GSH rxYFP [31,43,46,[199][200][201] roGFP1 [25][26][27][28][29]202,203] roGFP2 [12,19,33,[204][205][206] roGFP [207] eroGFP [35,36,[38][39][40][41][42]208] Grx1-roGFP2 [15,24,32,47,48,[209][210][211][212][213][214] general redox state rxRFP [30] Redoxfluor [44,215] H 2 O 2 HyPer…”
Section: Fungimentioning
confidence: 99%
“…Previous research revealed that Cys115 in the Cdc48 N-terminal domain undergoes oxidation during chronological aging which precedes massive thiol modifications emerging after the metabolic diauxic shift [454]. A paper by Radzinkski et al provides experimental evidence that Cys115 serves as a redox sensor crucial for sustaining Cdc48 cytosolic localization under conditions of oxidative stress, including that observed during senescence [48]. In this work, Grx1-roGFP2 allowed cellular populations with different E GSH to be isolated for investigation of the effect of the Cys115Ser substitution on their growth.…”
Section: Oxidative Stress In S Cerevisiaementioning
confidence: 99%
See 2 more Smart Citations